Islam and Buddhism: similarities of moral practices - Mohd Nor, Nur Suriya (IIUM Press, International Islamic University Malaysia, 2019)
Islamic moral system is not only defining morality, but also guides the human on how to achieve it, at both an individual as well as collective level. Buddhist morality is concerned with our relationship with ourselves and with other beings. This study shall focus on similarities of moral practices between Islam and Buddhism with a view of encouraging Buddhists to learn about the Islamic tradition and also to explain certain central concepts of Buddhism to Muslims who are unfamiliar with the Buddhist tradition as a way to increase their knowledge towards a better understanding of other religions. The similarities found between Islam and Buddhism would conduce acknowledgement and respect of one another on both sides. This is in keeping with the Qu‟rÉnic vision of mutual recognition and mutual respect i.e. taʿāruf between the Muslims and other world‟s communities and traditions as Allah mentioned in the Qu‟r`ān, Al-Hujurāt: 13.